Gestão de inventário de materiais - Patricio, Ricardo Kaltenbacher de Oliveira (2019)
This final project, according to the approach and methodology for the development of practical and applied work prepared by Marcondes, Michael, Franklin and Perez (2017) describes the problem solving in materials management in a logistics operation in a packaging company with high complexity and scale of production, with exclusive items from competing customers. Were identified fails in the inventory count controls, organization, layout, measurement tools, and technology definitions. In this way, a mapping of the operation was carried out and a plan was drawn up with proposals for solutions to the problem, in order to correct the failures that lead to the nonconformities of the material control. The actions have focused on the management model of the materials, applications, physical distribution, counts model and transaction validation logic. It was also considered technology implementation alternatives, such as RFID, WMS and UAVs as well as the application of training, professional development operational teams, and awards, recognition and implementation of a systemic process. During the process of innovation and construction of the final Project, a visit was made "in the field" for the validation and technical testimony funding for the foundation of the concepts that guided the proposals. In this way, the experience acquired in this work can be shared and replicated, for its future applicability, serving as the basis for the decisions of other companies of the same or different segments.